School-based factors affecting the teaching of kiswahili in public pre-schools in Kasipul division, Rachuonyo south sub-county, Homabay county - Omollo, George Odhiambo; Odongo, Benson Charles; Raburu, Pamela A. (International Journal of Education and Research, 2016)
Globally language is very important since it is a means of communication that leads to international development and cohesion. Kiswahili is a language taught in the pre-school curriculum in Kenya and a national language in the Republic of Kenya. Kiswahili has been faced with challenges in pre-schools emanating not only from teachers academic and professional preparation but also from attitude. This study focused on school based factors affecting the teaching of Kiswahili in pre-schools within Kasipul Division in Rachuonyo South sub-county. The study found out that there is language factors influencing learning of Kiswahili, the attitude of pre-school teachers was negative, several challenges face teaching of Kiswahili and the strategies used are not. Key Words: Learning; Teaching; Motivation; Achievement; School based factor